Tobacco smoking among physicians and medical students - Igić, Rajko; Bernaciak, Paula (Scripta Medica, 2022)
Tobacco smoking is a mental and behavioral disease. It causes significant pathology and premature death in more than seven million individuals a year around the globe. Because smoking is such important public health issue, the general public will benefit from targeted preventive strategies. Medical doctors have a vital role in smoking cessation of their patients. Non-smokers are more successful in this role than chronic smokers. Governmental regulation on smoking, as well as strict no-smoke policy in hospitals and university campuses will help not only medical students, other health workers and the general public to quit smoking and contribute to the general good health of this population. The aim of this comment is to analyse the current smoking habits of physicians and medical students and presents policies and other help to the medical students to stop tobacco smoking.
Keywords: Tobacco smoking; nicotine; e-cigarettes; tobacco module; nicotine repacement therapy; Smoking cessation